Evaluation of a collaborative testing approach to objective structured clinical examination (OSCE) in undergraduate nurse education: A survey study. (February 2019) - Saunders, Annette; Say, Richard; Visentin, Denis; McCann, Damhnat
Highlights: OSCEs are widely used but resource intensive and heighten student anxiety. Students responded positively to a unique OSCE design. Collaborative testing reduced anxiety, increased satisfaction and peer-learning.